The Why and Who Facets of Strategic Horticulture Enterprise Systems - Rachmaniah, Meuthia; Suroso, Arif Imam; Syukur, Muhamad; Hermadi, Irman (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Actual Indonesia's inflation rate is higher than the government's inflation target. One of the reasons is that the dataset for calculating food group inflation is asymmetric due to incomplete supply and demand data. This study tries to overcome asymmetric data constraints by providing an enterprise system for strategic horticultural commodities (SHES). The research method used the first three Zachman Framework perspectives: the executive perspective contextual view, the business management perspective conceptual view, and the architect's perspective physical view, each evaluated using the Why and Who facets. Respectively, the result of the Why facet is about business drivers and motivation intention: vision, mission, and goals; strategic goals and the SHES model's entity goals/objectives; and system development rules, requirements, and functionality representation. The Who facets results are associated with responsibility assignments of farmers, merchants, sub-district data collectors, District Agriculture offices, developers, users, and managers (tested using high-fidelity prototypes/mockups). With SHES, data and information collection becomes systematic and holistic, immediately in the form of real-time data from farmers and traders. Access to SHES uses the farmer's/trader's mobile phone. Thus, data recapitulation, from village to sub-district, district, to provincial and national, will likely be based on reality/data facts in the field. Keywords: Why and Who facets, real-time data, strategic horticultural commodities, high-fidelity prototype, Zachman framework